7 - Aide et Objectifs du Millénaire pour le Développement : un regard critique sur les stratégies de réduction de la pauvreté en Afrique subsaharienne - Maman, Abdo Hassan (Africa Development, 2021)
This article analyzes critically the aid destined to finance MGDs. It shows uncertainties linked to the financial Big Push promised in 2005 to Africa Sub-Saharan to catch up the gap in financing these goals. Not only this promise isn’t required but also the progresses of the realization of the MGDs are insufficient. This paper shows the limits of poverty reduction strategies which are subordinated to the donators priority goals: financial stabilization, good governance and credible institutions. They are not development strategies but the way to spend donators’ money. The big Push like Marshall Plan type cannot, regarding to the limits of capacity absorption of African countries, stimulate a necessary dynamic capable to transform the vicious circles of under-development in sustainable growth virtuous footpaths. The end of poverty passes by efforts to transform the African economic structures through an industrialization process within regional integration’s communities. This development animated by private structures and supported by authorities by long run and efficient strategies, would be able to create favorable conditions to get out definitively Africa Sub-Saharan to its ali entary, commercial dependence and its marginalization at World scale.